PERTUMBUHAN IKAN LELE SANGKURIANG (Clarias Gariepenus) PADA SISTEM RESIRKULASI - Lalu Sepi Al-Muhatir R.; Nanda Diniarti; Alis Mukhlis (Jurnal Media Akuakultur Indonesia, 2023)
Catfish is one of the commodities with promising prospects for development, both in hatchery and grow-out activities. One of the challenges in catfish farming is the high mortality rate of intensively raised fish without water exchange. In order to increase production, the implementation of good cultivation technologies is necessary to maximize the results. One such technology that can be used is the Recirculating Aquaculture System (RAS). This study aims to analyze the effects of RAS using lettuce plants as biofilters on the growth and survival of Clarias gariepinus catfish. The test animals used in this study were Clarias gariepinus catfish sourced from Beta Fish Lingsar Farm, with seed size ranging from 7-8 cm. The study was conducted with three treatments (plots): pond 1 = RAS with lettuce biofilter at a stocking density of 1000 individuals, pond 2 = RAS with a stocking density of 1000 individuals, and pond 3 = RAS with a stocking density of 500 individuals. The results of the study showed that the use of the RAS system had an impact on the growth and survival of the fish. The RAS system with lettuce biofilter was able to increase the Specific Growth Rate (SGR) by 6.02% and reduce fish mortality rate with a Survival Rate (SR) value of 62.8%. Based on these findings, the use of RAS with plant biofilters can be further developed on a larger scale in aquaculture.